'Time isn't after us': some Tiresian Durations. (March 2017) - Salah, Trish
Abstract : Drawing upon Jean Laplanche's thinking around afterwardness as translation, this article is an attempt to consider some temporal rhetorics conditioning contemporary possibilities for transgender, genderqueer and transsexual self-representation. It will look particularly to aesthetic problems of inscription, for instance texts figuring a wish for antecedents/ancestors (such as the Greek seer, Tiresias), as well as at the deferred action of fantasies underpinning early psychoanalytic interpretation of cross sex identification ('the Schreber case') and consider how such readings or fantasies might affect, even organize, contemporary sexual minority identities and relations. Further it will bring these questions into relation with the effacement of recent transsexual cultural production and activism at the transgender 'tipping point' while attempting to disinter and make available for re-translation subalterned histories and possibilities occluded by, if haunting, a century of psychoanalytic, feminist and queer progress.